Who Did What to Whom? The Relationship Between Syntactic Aspects of Sentence Comprehension and Text Comprehension. (3rd July 2016) - Poulsen, Mads; Gravgaard, Amalie K. D.
ABSTRACT: This study investigated the relationship between syntactic comprehension at the sentence level and text-level comprehension. The study isolated the specific contribution of syntax by asking whether sentence comprehension efficiency of difficult syntactic constructions explained variance in text comprehension after controlling for sentence comprehension efficiency of basic constructions with similar semantic complexity. Seventy-three Grade 5 students completed assessments of text comprehension; basic and difficult written sentence comprehension efficiency; and control measures of decoding fluency, vocabulary, and verbal memory. Efficiency measures were used to assess individual differences in basic sentence comprehension with accuracy near ceiling. Difficult sentence comprehension efficiency explained 6% unique variance in text comprehension after controlling for basic sentence comprehension efficiency and other controls. Thus, the results show that individual differences in the ability to establish sentence meaning from syntactic information are related to text comprehension.